MEDIASI KEPUASAN KERJA PADA PENGARUH STRESS KERJA TERHADAP TURNOVER INTENTION KARYAWAN - Rasmen Adi, I Nyoman; Gede Elvina Adi Saputri, Luh; Mulyadi, Made; Meryawan, I Wayan (CV. Lafadz Jaya, 2024)
This research aims to examine the influence of work stress and the mediating role of job satisfaction on employee turnover intention at the Anumana Ubud Hotel. This study involved 98 respondents selected using the total sampling method. Data was collected via a Likert scale questionnaire and analyzed using SEM-PLS. Hypothesis testing was carried out with a one-sided t-test. The research results show that work stress has a significant positive influence on turnover intention, as well as a significant negative influence on employee job satisfaction. Apart from that, job satisfaction has a significant negative effect on turnover intention. Job satisfaction acts as a partial mediator in the relationship between job stress and turnover intention. This research model has a predictive relevance (Q2) of 0.514 which is considered strong.